Explicit and Implicit Manageable Reactive Focus-On-Form Strategies as Determinants of Senior Secondary School Students’ Learning Outcomes in English Essay Writing (2014)
English Language is the most compulsory subject in school curricular in Nigeria. As an important subject at secondary school, success or failure in it determines the extent to which learners would advance in their educational and career pursuits in life. However, records from public examination bodies reveal that students’ performance in the subject has been below average. This has been traced to their poor performance in and attitude to essay writing aspect of English Language examination which is poorly handled with traditional teaching strategies. Hence, there is need to adopt teaching strategies that address these deficiencies; two of which are explicit and implicit manageable reactive focus-on-form. Studies reported the effectiveness of these strategies in teaching oral communication without consideration for their effects on students’ learning outcomes in essay writing. Therefore, this study examined the effects of explicit and implicit manageable reactive focus-on-form strategies on students’ learning outcomes in essay writing in Ogun East Senatorial District of Ogun State. The moderating effects of class size and self-esteem were also determined. The study adopted the pretest-posttest, control group quasi-experimental design. Participants were 335 senior secondary two students in intact classes from nine purposively selected secondary schools. The schools were randomly assigned to explicit and implicit manageable reactive focus-on-form and conventional strategies. Treatment lasted twelve weeks. Nine instruments were used: Achievement Test in Essay Writing (r=0.70), Attitude to Essay Writing Questionnaire (r=0.72), Self-Esteem Questionnaire (r=0.84), Manuals on Explicit and Implicit Error Identification, Teachers’ Evaluation Sheet, Instructional Guides for Explicit and Implicit Manageable Reactive focus-on-form and Conventional Strategy. Seven null hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance and Scheffe post hoc. Treatment had a significant main effect on achievement in essay writing (F(3,331) =204.43, R2=.43). Students in the Implicit group had a higher achievement mean score (x =25.00) than those in the Explicit (x=23.25) and the control (x=18.44) groups. Treatment had no significant main effect on attitude to essay writing. Class size had a significant main effect on achievement (F (3,331)=15.81, R2=.14) but not on attitude. Students in small class size had higher achievement mean score (x= 24.71) than medium (x=22.26) and large class size (x=20.45). Self-esteem had no significant main effect on achievement in and attitude to essay writing. There was a significant interaction effect of treatment and class size on achievement (F (9,325)=4.23, R2=.26) but not on attitude. The 3-way interaction effects of treatment, class size and self-esteem were not significant on achievement and attitude. Explicit and Implicit manageable focus-on-form strategies are effective in enhancing students’ learning outcomes in English composition especially in small classes. Hence, teachers should adopt these strategies for effective essay writing instruction in schools with small class sizes in order to reduce learners’ errors in English composition.